2019
DOI: 10.1038/s42003-019-0680-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signature of an ancient organizer regulated by Wnt/β-catenin signalling during primary body axis patterning in Hydra

Abstract: Wnt/β-catenin signalling has been shown to play a critical role during head organizer formation in Hydra. Here, we characterized the Wnt signalling regulatory network involved in formation of the head organizer. We found that Wnt signalling regulates genes that are important in tissue morphogenesis. We identified that majority of transcription factors (TFs) regulated by Wnt/β-catenin signalling belong to the homeodomain and forkhead families. Silencing of Margin, one of the Wnt regulated homeodomain TFs, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…Following MEME-ChIP, the obtained motifs were submitted to TOMTOM in MEME-Suite to identify the TF that binds to the intergenic region. RNA-seq data generated previously in the lab [19] was used to show transcription over the selected peak regions (SAMN08966965).…”
Section: Chip-seq Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Following MEME-ChIP, the obtained motifs were submitted to TOMTOM in MEME-Suite to identify the TF that binds to the intergenic region. RNA-seq data generated previously in the lab [19] was used to show transcription over the selected peak regions (SAMN08966965).…”
Section: Chip-seq Analysismentioning
confidence: 99%
“…This makes Hydra an ideal model system to study the process of axis patterning where the primary longitudinal axis is the oral-aboral axis. We have identified the downstream molecular players of the Wnt/β-catenin signaling pathway which resulted in the identification of multiple homeobox transcription factors that play a critical role in Hydra axis formation [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, it is unclear how Eco peptides antagonize the Wnt pathway, but we assume that they act downstream of β-catenin, given the following arguments. First, we showed that Eco-KD animals have a higher probability of forming tentacles after ALP treatment but have normal regeneration capability; thus, Rax could be a target transcription factor inhibited upon Eco signaling (67). Secondly, we showed that low temperature is antagonizing the effect of overexpressed β-catenin.…”
Section: Discussionmentioning
confidence: 86%
“…But none of them seem to resemble all assumed properties of the HI in the Gierer–Meinhardt model. Further, several downstream genes of the Wnt-signaling pathway have been shown to be involved in specific aspects of Wnt signaling: For example, the homeobox gene rax is important for tentacle formation ( 67 ), PKC signaling seems to be important for head regeneration ( 68 ), but not in bud formation ( 69 ), while ERK signaling was essential for both processes ( 68 , 69 ). We thus argue that several levels of Wnt inhibition exist and that the activity of Eco peptides provides one mechanism.…”
Section: Discussionmentioning
confidence: 99%